IMPROVING IPAS LEARNING OUTCOMES ON THE SOLAR SYSTEM TOPIC THROUGH THE IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL ASSISTED BY AUDIO-VISUAL MEDIA FOR FIFTH-GRADE STUDENTS AT SDN 7 DUNGALIYO, GORONTALO REGENCY - Dewi Rahmawati jafar; Gamar Abdullah; Meylan saleh; Vicka muniati arifin; Nurfadliah (Journal of Education and Teaching Learning, 2026)
in this study is whether the implementation of the Discovery Learning model assisted by audio-visual media can improve Natural and Social Sciences (IPAS) learning outcomes on the solar system topic for fifth-grade students at SDN 7 Dungaliyo. This study aims to improve the IPAS learning outcomes on the solar system topic for fifth-grade students at SDN 7 Dungaliyo through the implementation of the Discovery Learning model assisted by audio-visual media. This type of research is Classroom Action Research (CAR). Data collection techniques in this study included observation, interviews, tests, and documentation. During the initial observation, the students' achieved abilities were still very low, with only 4 students (22%) attaining high IPAS learning outcomes or scoring above the Learning Objective Achievement Criteria (KKTP). In the implementation of Cycle I, an increase was observed, reaching 8 students (44.4%). However, this result had not yet met the established classical mastery criteria of 70%, necessitating the continuation of the research into the next cycle, Cycle II. In Cycle II, there was an increase in student learning mastery, reaching 16 students (88.9%). The results of the study indicate that the implementation of the Discovery Learning model assisted by audio-visual media significantly improves IPAS learning outcomes on the solar system topic for fifth-grade students at SDN 7 Dungaliyo.